HUBUNGAN KEBIASAAN MAKAN DENGAN KEJADIAN OSTEOPOROSIS PADA LANSIA DI PUSKESMAS KUTALIMBARU KECAMATAN KUTALIMBARU KABUPATEN DELI SERDANG - Purwaningsih Purwaningsih; Ade Irma Khairani (Akademi Keperawatan Kesdam I/Bukit Barisan Medan, 2018)
Based on WHO data, osteoporosis is classified into 10 main degenerative diseases in the world there are ± 2000 million patients in the world with osteoporosis. In Indonesia, 19.7% of the elderly or 3.6 million of people with osteoporosis. The increasing of incident of osteoporosis is related to the age and bad eating habits. The objective of this research is to analyze a correlation between the eating habit and osteoporosis to the elderly.This research was an analytic study with case control approach. This research was conducted in Puskesmas Kutalimbaru Regency of Deli Serdang. The population of this research were 190 persons. The sample was divided into 2 group (each group is consist of 95 persons). The analysis was univariable, bivariable using chi square and multi variable using multi logistic regression.The result of research indicates that the eating habit of elderly was related to the incident of osteoporosis significantly in Puskesmas Kutalimbaru sub district of Kutalimbaru, Regency of Deli Serdang, diet portion (p = 0.005, OR = 3.374), coffee consumption (p = 0.000, OR = 4.116) and green vegetables consumption (p; = 0.013, OR = 2.399). while variable that did not related to the osteoporosis to the elderly was water drink ( p = 0.512), milk consumption (p = 0.094) and fresh fruit consumption (p = 0.385). the dominant variable related to the osteoporosis to the elderly was coffee consumption. The elderly who always consume coffee has a risk for osteoporosis 4.1 higher than elderly who did not or never consume coffee.The conclusion of this research is the osteoporosis to the elderly is related to the diet portion, consumption of coffee and green vegetables. It is suggested to the Puskesmas Kutalimbaru to provide the extension of health promotion about the nutrition content to the society with the target of elderly through society activities such as society gathering or religion gathering.Keywords : Eating Habit, Osteoporosis, Elderly